Solid Phase Extraction and Flame Atomic Absorption Spectrometry for the Determination of Trace Thallium - LI, YINKE; PENG, YONGFANG; MA, YINHAI; HU, QIUFEN; YANG, GUANGYU (Asian Journal of Chemistry, 2010)
Based on the separation and preconcentration of thallium(III) by solid phase extraction with N-(3,5-dimethylphenyl)-N'-(4-aminobenzenesulfonate) thiourea (DMMPT) loaded on graphitized carbon black as a sorbent, a new method for the determination of thallium was developed. The preconcentrated Tl(III) was eluted from the cartridge with 1.0 mL of 0.5 mol L-1 HNO3 as eluant and then the thallium(III) contents was measured by flame atomic absorption spectrometry. Under the optimum conditions, a preconcentration factor of 1000 was achieved. The detection limit of the method reaches 0.05 μg L-1. The method was successfully applied for the determination of thallium in biological sample and water. The relative standard deviations were below 3.4 % with recoveries of 88-106 % and the determination results were agreed with that of reference method.